2020
DOI: 10.26444/aaem/115178
|View full text |Cite
|
Sign up to set email alerts
|

Adverse health outcomes among workers of wood pellet production facilities

Abstract: Introduction. Workers of pellet production facilities (WPPF) are exposed to high concentrations of wood dust and microbial pollutants. Such stimulation may lead to numerous allergic and toxic reactions, infections, and other non-specific syndromes. Objective. To check the influence of individual traits of workers and characteristic features / factors of their living and working environments on the probability of adverse outcomes' appearance. Materials and Method. The questionnaire study assessing adverse healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…A review of occupational exposures to wood dust in the European Union suggested that workers in construction, furniture, builders' carpentry, joinery, sawmilling and forestry were the highest exposed [5]. Furthermore, high exposures have also been reported in plywood and chipboard factories, pulp and paper mills, composting, wood pellet production, and use of wood chips in biofuel or bedding for animals [2,6]. Studies on the African continent have also reported excessive dust exposures in small to large-scale wood factories and particleboard companies [1].…”
Section: Occupations and Populations At Riskmentioning
confidence: 99%
See 2 more Smart Citations
“…A review of occupational exposures to wood dust in the European Union suggested that workers in construction, furniture, builders' carpentry, joinery, sawmilling and forestry were the highest exposed [5]. Furthermore, high exposures have also been reported in plywood and chipboard factories, pulp and paper mills, composting, wood pellet production, and use of wood chips in biofuel or bedding for animals [2,6]. Studies on the African continent have also reported excessive dust exposures in small to large-scale wood factories and particleboard companies [1].…”
Section: Occupations and Populations At Riskmentioning
confidence: 99%
“…wood dust particulate (0.09–25 mg/m 3 ), endotoxins (2.5–62.2 ng/m 3 ) and fungal spores (0.4–4 × 10 5 particles/m 3 ) (Table 1). In wood pellet production facilities (WPPF) wood dust particulate, microorganisms, endotoxin and (1→3)-β- d -glucan concentrations can reach higher values of up to 65 mg/m 3 , 19320 CFU/m 3 , 215 ng/m 3 and 1525 ng/m 3 , respectively [2].…”
Section: Exposure Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12] There are many studies and case reports that link numerous allergic and toxic reactions, including infections by microbial pollutants clinging to the wood dust. 13 A study of exposure levels to wood dust was reported to be over the limit among the workers, and the Swedish occupational exposure limit (OEL) of 2 mg/m 3 of inhalable dust were exceeded by one third of the measurements and were, on average, 3.2 times higher than total dust. 14 Exposure to wood dust from sawmills has been shown to increase the risk of developing lung function deficits and respiratory symptoms.…”
mentioning
confidence: 99%